2009
DOI: 10.1002/mnfr.200800274
|View full text |Cite
|
Sign up to set email alerts
|

Albumin stabilizes (–)‐epigallocatechin gallate in human serum: Binding capacity and antioxidant property

Abstract: (-)-Epigallocatechin gallate (EGCg) is the major component of green tea and is known to show strong biological activity, although it can be easily oxidized under physiological conditions. In this study, we indicate that EGCg is stable in human serum and that human serum albumin (HSA) stabilizes EGCg under aerobic condition. Although EGCg is usually decomposed within 1 h in aqueous solution at neutral pH, EGCg in serum and phosphate buffer (pH 7.4) containing HSA was stable over 1 h, even at neutral and slightl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 34 publications
5
67
0
1
Order By: Relevance
“…That lipid peroxidation was not increased may be due to ROS scavenging by antioxidant enzymes and/or suppression of ROS generation by cysteinyldopa and quinoprotein formation through the binding of dopaquinone and dopaminequinone with cysteine. 10,30,31) Another research group hypothesized that l-DOPA inhibited growth of soybean may be by activation of a phenylalanine ammonia-lyase (PAL) and phenylpropanoid pathway thus accumulating phenolic compounds-including lignin-and increasing peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…That lipid peroxidation was not increased may be due to ROS scavenging by antioxidant enzymes and/or suppression of ROS generation by cysteinyldopa and quinoprotein formation through the binding of dopaquinone and dopaminequinone with cysteine. 10,30,31) Another research group hypothesized that l-DOPA inhibited growth of soybean may be by activation of a phenylalanine ammonia-lyase (PAL) and phenylpropanoid pathway thus accumulating phenolic compounds-including lignin-and increasing peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) We have previously reported that the binding capacity of HSA contributed to the stabilization of EGCg and that HSA prevented EGCg oxidation by its antioxidative activity. 17) Furthermore, the hydroxyl groups on the galloyl group and the number of hydroxyl groups on the B-ring of each catechin have influenced the binding affinity for HSA in an acidic solution with acetonitrile by HPLC with an HSA column. 25) However, the mechanism for EGCg stabilization has not previously been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…16) In addition, we have previously shown that EGCg was stable in human serum even at a slightly alkaline pH level and that the antioxidative property and binding capacity of human serum albumin (HSA) contributed to the stabilization of EGCg in serum. 17) EGCg is therefore thought to be stable under anaerobic conditions in vivo, although the mechanism for EGCg stabilization has not yet been characterized in detail.…”
mentioning
confidence: 99%
“…Several reports using spectrofluorometry, circular dichroism, and capillary electrophoresis have indicated that green tea catechins bind to HSA (12)(13)(14). Recently, we revealed that EGCg non-covalently binds to HSA after incubation of human serum with EGCg ( 15 ). In a separate study, we demonstrated, using high performance liquid chromatography (HPLC) with an immobilized HSA column, that the hydroxyl groups on the galloyl moiety and the number of hydroxyl groups on the B-ring of each catechin influence binding affinity toward HSA under acidic conditions ( 16 ).…”
mentioning
confidence: 87%